Optimum design of a vortex tube for achieving large temperature drop ratios - Westley, R. (College of Aeronautics, Cranfield, 1955)
The vortex tube, invented by G.J. Ranque, is a simple device which separates a flow of compressed gas into a hot and a cold stream by means of a high speed vortex. It may have useful applications as a refrigerator and one of the aims of the present investigation was to widen the field of application by increasing the vortex tube's cooling performance. The tests, described in this report, determined the effect of the hot valve setting, the cold outlet diameter, the inlet nozzle size and the inlet pressure ratios, upon the temperature drop ratio characteristics of a vortex tube. The results show that, by matching the inlet nozzles and cold outlet diameter to the inlet pressure ratio, it is possible to obtain, over a wide pressure range, a temperature drop which is 0.50 of the isentropic temperature drop. The optimum cold outlet area is almost independent of the inlet pressure, whilst the optimum inlet area decreases as the pressure ratio increases.